The Use of Video to Improve the Eighth Grade Students’ Achievement in Writing Descriptive Text at SMP Negeri 5 Bondowoso - Rizky Kurnia R. P; Budi Setyono; Eka Wahjuningsih (FKIP e-PROCEEDING, 2017)
Abstract: This research was intended to describe how the use of photo montage video can improve the eighth grade students’ achievement in writing descriptive text at SMP Negeri 5 Bondowoso. This research used Classroom Action Research (CAR) as the research design which consisted of planning, action, observing, and reflecting. The research subject were 23 students of class VIII D at SMP Negeri 5 Bondowoso. The data was collected by observation and writing test. Based on the result of observation, it was found that the use of photo montage video helped the students in planning descriptive text through vocabulary, content, and organization. The use of photo montage video also had contribution in helping students to draft a descriptive text through content and organization. Moreover, the use of photo montage video also helped the students in revising descriptive text.  Meanwhile, there were 66.66 % of the students got at least 75 or higher in writing test in cycle 1. Based on the writing test in cycle 2, there were 80.95% of the students got at least 75 or higher. According to the result of the research, it was concluded that the use of photo montage video improved the students’ achievement in writing descriptive text. Keywords: Photo Montage Video, Classroom Action Research, Descriptive Text, Writing Achievement